Suboptimal initiation predicts short‐term prognosis and vulnerability among very elderly patients who start haemodialysis. Issue 1 (16th December 2018) - Kanno, Atsuhiro; Nakayama, Masaaki; Sanada, Satoru; Sato, Mitsuhiro; Sato, Toshinobu; Taguma, Yoshio
ABSTRACT: Aim: A recent, growing concern regarding haemodialysis in Japan is a sustained increase in the elderly population. Among very elderly people who start haemodialysis, the prognosis is considered to be poor; however, this has not been fully elucidated. This study aimed to discover the short‐term prognosis and related factors in very elderly patients who commence haemodialysis. Methods: Between January 2008 and December 2013, 122 patients aged ≥85 years at haemodialysis initiation were documented in our hospital. Predictors of 90‐day and 1‐year mortality after haemodialysis initiation were assessed with Cox proportional hazards regression analysis. Selection of covariates for the multivariate model was based on forward stepwise selection using the probability of a likelihood ratio statistics. Results: The subjects' mean age was 87.4 ± 2.5 years, and 48% were female. The most common cause of death was infection (38% of patients) and the leading cause of infectious death was pneumonia. The 90‐day and 1‐year survival rates were 81% and 62%, respectively. Suboptimal initiation was a significant prognostic factor for 90‐day [hazard ratio (HR) 3.98, 95% confidence interval (CI) 1.18–13.43] and 1‐year [HR 3.19, 95% CI 1.51–6.76] mortality after adjusting for confounders in multivariate analysis. Conclusion: Very elderly patients who started haemodialysis had a poor prognosis, and suboptimal initiation significantly predicted outcome. Shared decision‐making with patients and their families is needed for initiating haemodialysis on the conditions that appropriate information on the expected prognosis is provided. Summary at a Glance: In very elderly patients commencing dialysis in Japan, 46 of 122 patients studied died over the next 12 months, 22 of these within 3 months. More than half started haemodialysis with a temporary catheter and this group, called 'suboptimal initiation', were notable for their poorer performance status and greater mortality risk. This manuscript raises important issues about the management of end‐stage kidney disease in the very elderly in Japan.